RESPOSTAS DE CULTIVARES DE ARROZ (ð˜–ð˜³ð˜ºð˜»ð˜¢ ð˜´ð˜¢ð˜µð˜ªð˜·ð˜¢ L.) AO ALUMÃNIO EM SOLUÃ‡ÃƒO NUTRITIVA - Fahl, Joel Irineu; Carelli, Maria Luiza Carvalho; Deuber, Robert; Nogueira, Sandra dos Santos SevÃ¡ (REVISTA DE AGRICULTURA, 2020)
RESPOSTAS DE CULTIVARES DE ARROZ (ð˜–ð˜³ð˜ºð˜»ð˜¢ ð˜´ð˜¢ð˜µð˜ªð˜·ð˜¢ L.) AO ALUMÃNIO EM SOLUÃ‡ÃƒO NUTRITIVA